The Use of Booklet Media in Earthquake Natural Disaster Mitigation Socialization Activities on the Knowledge of Students of Public Elementary School - Tarisa Fitrah, Iftitah Hanim Tarisa Fitrah; Wulan Purnama, Laila Cahyani; Ummah, Mazroatul Khoiroh Ummah; Amanina, Naura Hanin; Amelia, Talitha; Usraturrahmah (Tarqabin Nusantara Group, 2025)
Mitigation is a series of activities carried out to reduce disaster risk and is included in the initial stages of natural disaster management. Activities to provide information and mitigate disasters are one of our responsibilities as academics who are aware of this problem to the general public, one of the targets being PAUD or Elementary School students. In recent years, the Central Board of Education's move to revise the curriculum to include disaster prevention into subjects is fully underway. Therefore, we are carrying out community service to mitigate natural earthquake disasters which will be held on Friday 3 May 2024 at SDN 4 Tumpang, Tumpang District, Malang Regency, which is one of the schools that includes prevention as a subject in its school. The results of this research indicate that the use of booklet media can be an effective method in increasing students' knowledge regarding earthquake natural disaster mitigation at the elementary school level. This can be seen from students who took part in the socialization showing a significant increase in understanding after being given material and information through print media. Booklet media designed with animation and attractive images can attract students' attention and make it easier for them to understand the material presented. Apart from that, the pre-test and post-test conducted before and after socialization also showed a significant increase in student knowledge.